2020
DOI: 10.1146/annurev-arplant-050718-095955
|View full text |Cite
|
Sign up to set email alerts
|

Redox Homeostasis and Signaling in a Higher-CO2World

Abstract: Rising CO2 concentrations and their effects on plant productivity present challenging issues. Effects on the photosynthesis/photorespiration balance and changes in primary metabolism are known, caused by the competitive interaction of CO2 and O2 at the active site of ribulose-1,5-bisphosphate carboxylase/oxygenase. However, impacts on stress resistance are less clear. Reactive oxygen species are key players in biotic and abiotic stress responses, but there is no consensus on whether elevated CO2 constitutes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 149 publications
1
59
0
Order By: Relevance
“…ROS scavenging is performed enzymatic or via non-enzymatic antioxidant defense pathways, which control the regulation of ROS levels through strict compartmentalization (Mignolet-Spruyt et al, 2016;Noctor et al, 2017;Foyer and Noctor, 2020). Non-enzymatic antioxidant defense is mainly mediated by low molecular-weight metabolites such as ascorbate, glutathione, α-tocopherol, carotenoids, and flavonoids (Locato et al, 2017;Smirnoff, 2018;Zechmann, 2018;Muñoz and Munné-Bosch, 2019;Foyer and Noctor, 2020). Superoxide dismutases (SODs), catalases (CATs), ascorbate peroxidases (APXs), dehydroascorbate reductases (DHARs), monodehydroascorbate reductases (MDHARs), and glutathione reductases (GRs) are among the main antioxidant enzyme classes.…”
Section: Characterization Of Key Antioxidant Enzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS scavenging is performed enzymatic or via non-enzymatic antioxidant defense pathways, which control the regulation of ROS levels through strict compartmentalization (Mignolet-Spruyt et al, 2016;Noctor et al, 2017;Foyer and Noctor, 2020). Non-enzymatic antioxidant defense is mainly mediated by low molecular-weight metabolites such as ascorbate, glutathione, α-tocopherol, carotenoids, and flavonoids (Locato et al, 2017;Smirnoff, 2018;Zechmann, 2018;Muñoz and Munné-Bosch, 2019;Foyer and Noctor, 2020). Superoxide dismutases (SODs), catalases (CATs), ascorbate peroxidases (APXs), dehydroascorbate reductases (DHARs), monodehydroascorbate reductases (MDHARs), and glutathione reductases (GRs) are among the main antioxidant enzyme classes.…”
Section: Characterization Of Key Antioxidant Enzymesmentioning
confidence: 99%
“…Superoxide dismutases (SODs), catalases (CATs), ascorbate peroxidases (APXs), dehydroascorbate reductases (DHARs), monodehydroascorbate reductases (MDHARs), and glutathione reductases (GRs) are among the main antioxidant enzyme classes. Furthermore, glutathione peroxidases, peroxidases, and thio-, gluta-, and peroxiredoxins are potent ROS scavengers as well (Dietz, 2011;Kang et al, 2019;Foyer and Noctor, 2020). Within this section, we briefly characterize the key enzymatic antioxidants in plants.…”
Section: Characterization Of Key Antioxidant Enzymesmentioning
confidence: 99%
“…In silico gene expression data (Miyazaki et al, 2004;Li et al, 2006) also indicated that CE up-regulates many genes associated with redox control and thus impairment in ROS balance. Recently, Foyer and Noctor (2020) also concluded that apoplastic ROS signals were increased at high CO 2 , and possibly due to the involvement NADPH oxidases (Cheeseman, 2006;Qui et al, 2008;Mhamdi and Noctor, 2016). Although CE helps in the retention of chlorophyll pigment (Li et al, 2019), it might also lead to production of toxic ROS and RNS (reactive nitrogen species) like nitric oxide (NO) (Adavi and Sathee, 2018;Foyer and Noctor, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, information has become increasingly available indicating that photorespiration can influence various biological processes, e.g., carbon metabolism, energetics, nitrogen assimilation, and respiration [ 29 31 ]. Remarkably, photorespiration is a major source for H 2 O 2 in photoautotrophic tissues, thereby making important contributions to cellular redox status and signaling [ 2 , 11 , 30 ]. Reports indicate that H 2 O 2 is closely associated with IAA during plant development, and that IAA can facilitate H 2 O 2 accumulation in the roots of maize, tomato, and Arabidopsis to regulate root growth and gravitropism [ 32 34 ], while IAA biosynthesis and signaling were inhibited by both exogenous and endogenous H 2 O 2 in Arabidopsis seedlings [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…After reaching the four-leaf stage, seedlings were transplanted, either being continuously grown in Kimura B complete nutrient solution in a plant growth chamber with a light cycle of 14 h light/10 h dark (30 °C / 25 °C, respectively) at 600 µmol photons m −2 s −1 on average, relative humidity 60%-80%, or grown in paddy fields under natural conditions. For high concentration CO 2 treatment, pre-germinated rice seeds were cultured in Kimura B complete nutrient solution in a plant growth chamber (Percival E-41HO, USA) supplied with 3500 ppm CO 2 [ 30 , 54 , 55 ].…”
Section: Methodsmentioning
confidence: 99%